2017
DOI: 10.4196/kjpp.2017.21.5.465
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol raises in vitro anticancer effects of paclitaxel in NSCLC cell line A549 through COX-2 expression

Abstract: The aim of this study was to determine the raising anticancer effects of resveratrol (Res) on paclitaxel (PA) in non-small cell lung cancer (NSCLC) cell line A549. The 10 µg/ml of Res had no effect on human fetal lung fibroblast MRC-5 cells or on A549 cancer cells and the 5 or 10 µg/ml of PA also had no effect on MRC-5 normal cells. PA-L (5 µg/ml) and PA-H (10 µg/ml) had the growth inhibitory effects in NSCLC cell line A549, and Res increased these growth inhibitory effects. By flow cytometry experiment, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Hence, this combination enhanced apoptotic effects in DBTRG cells. Similarly, another study showed that RESV increased the anticancer effects of PAX through upregulation of apoptosis and caspase 3 in non-small cell lung cancer [ 86 ] and HepG2 cancer cell lines [ 12 , 87 , 88 ]. Our data shows that PAX and RESV treatment enhances apoptosis in a caspase-9-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this combination enhanced apoptotic effects in DBTRG cells. Similarly, another study showed that RESV increased the anticancer effects of PAX through upregulation of apoptosis and caspase 3 in non-small cell lung cancer [ 86 ] and HepG2 cancer cell lines [ 12 , 87 , 88 ]. Our data shows that PAX and RESV treatment enhances apoptosis in a caspase-9-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Stilbenoids including resveratrol are non-nitrogenous polyphenols with acidic and amphiphilic characters with anti-inflammatory activity. Many of their targets are occurring on cyclooxygenase (COX), 5-lipoxygenase (5-LOX) and protein kinase B [ 92 ], which is associated with its ability to inhibit COX-1 and COX-2 activity along with transcription factors activity inhibition, directly involved in COX activity regulation [ 93 ]. Studies reported the ability of resveratrol to reduce the secretion and expression of inflammatory factors [ 94 ].…”
Section: Biological Activities Of Resveratrolmentioning
confidence: 99%
“…Previous studies have shown that lauric acid and resveratrol have anticancer effects and are useful in the management of various cancers. [10][11][12][13][14][15][16][17][26][27][28] . Compound 2 is a synthetic substance, synthesized from lauric acid and resveratrol.…”
Section: Discussionmentioning
confidence: 99%